2012
DOI: 10.1097/gme.0b013e3182290b26
|View full text |Cite
|
Sign up to set email alerts
|

Vascular resistance of central retinal and ophthalmic arteries in postmenopausal women after use of tibolone

Abstract: Our study demonstrates that tibolone administration to healthy postmenopausal women does not affect the resistance of small-caliber cerebral arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Ultrasonography of the ophthalmic artery is a well‐established imaging modality and has been utilized for studying a variety of non‐obstetric pathologies, including glaucoma, heart failure, systemic atherosclerosis and multiple sclerosis. In the gynecological context, it has been demonstrated that use of tibolone by healthy postmenopausal women does not alter the Doppler indices of this vessel. Ophthalmic Doppler sonography is well tolerated by patients and does not take long to perform.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography of the ophthalmic artery is a well‐established imaging modality and has been utilized for studying a variety of non‐obstetric pathologies, including glaucoma, heart failure, systemic atherosclerosis and multiple sclerosis. In the gynecological context, it has been demonstrated that use of tibolone by healthy postmenopausal women does not alter the Doppler indices of this vessel. Ophthalmic Doppler sonography is well tolerated by patients and does not take long to perform.…”
Section: Introductionmentioning
confidence: 99%
“…18 In an RCT with placebo in a group of 100 healthy postmenopausal women younger than 65 years, tibolone did not affect the resistance of small-caliber cerebral arteries. 27 Finally, in other cohort studies or in RCTs in which the objective was not the consideration of cardiovascular events, no more myocardial infarction or stroke was observed with tibolone, perhaps because the age of the women studied was closer to the age at natural menopause. 28 …”
Section: Cardiovascular Effectsmentioning
confidence: 97%